A novel method for evaluating hot mix asphalt fatigue damage: X-ray computed tomography. (15th June 2016) - Shaheen, Magdy; Al-Mayah, Adil; Tighe, Susan
Highlights: An innovative image-based method was employed for the quantification of air voids and fatigue damage. Asphalt beams were scanned using X-ray CT prior to and following the four-point bending test. Both 2D and 3D image analysis proved suitable for evaluating HMA fatigue damage. The developed method was applied to evaluate and rank the asphalt beams fatigue performance. Abstract: This paper presents a framework for employing X-ray computed tomography (CT) for the assessment of hot mix asphalt (HMA) fatigue damage. The analyses were carried out on asphalt beams in order to quantify the damage created by four-point bending load. A new algorithm has been developed for calculating the thresholding levels of the images acquired before and after testing. The thresholding level prior to testing was estimated using laboratory air voids. To determine the post-testing thresholding level, the proposed algorithm matches 16-bit image histograms obtained before and after the test. This process is implemented only for the portion of the histogram that represents the aggregate colour intensities that remain unchanged during the testing. The results and analysis reveal that the developed technique is a valid method for successfully quantifying and evaluating HMA fatigue damage in large specimens. Because of the high degree of precision they provide, 16-bit images are recommended for this type of analysis. It was found that the distributions of air voids and damage are not uniform in asphalt beams and that they vary significantly throughout the length of a single beam as well as from beam to beam. This study also confirms the effectiveness of X-ray CT for quantifying HMA fatigue damage in asphalt beams following crack propagation.